1997
DOI: 10.1029/96wr03848
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of annual maximum series and partial duration series methods for modeling extreme hydrologic events: 1. At‐site modeling

Abstract: Abstract. Two different models for analyzing extreme hydrologic events, based on, respectively, partial duration series (PDS) and annual maximum series (AMS), are compared. The PDS model assumes a generalized Pareto distribution for modeling threshold exceedances corresponding to a generalized extreme value distribution for annual maxima. The performance of the two models in terms of the uncertainty of the T-year event estimator is evaluated in the cases of estimation with, respectively, the maximum likelihood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
236
0
11

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(254 citation statements)
references
References 36 publications
1
236
0
11
Order By: Relevance
“…Beside block maxima, peaks-over-the threshold series (POT), also known as a Partial Duration Series (PDS), are frequently used to assess the behavior of extreme events [see Madsen et al, 1997;Lang et al, 1999]. It can be shown that a connection exists between the models typically used to estimate flood frequency using either block maxima or the POT series, and both methods would asymptotically lead to equivalent inference.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beside block maxima, peaks-over-the threshold series (POT), also known as a Partial Duration Series (PDS), are frequently used to assess the behavior of extreme events [see Madsen et al, 1997;Lang et al, 1999]. It can be shown that a connection exists between the models typically used to estimate flood frequency using either block maxima or the POT series, and both methods would asymptotically lead to equivalent inference.…”
Section: Introductionmentioning
confidence: 99%
“…It can be shown that a connection exists between the models typically used to estimate flood frequency using either block maxima or the POT series, and both methods would asymptotically lead to equivalent inference. The performance of different estimation methods applied to block maxima and POT series are discussed in Madsen et al [1997]. The analysis of threshold exceedances would potentially be a better tool to detect and attribute the effect of different variables on the high-flow properties as this would ensure that a larger number of data points (all characterizing the extremal part of the distribution) are used to investigate the effects of the variables on high flows.…”
Section: Introductionmentioning
confidence: 99%
“…This value should be low enough to ensure the inclusion of as much relevant information as possible, without violating the assumption of independence of the peaks. Various methods have been proposed to determine the most appropriate lower bound (Ashkar and Rouselle, 1987;Madsen et al, 1997a). However, Beguería (2003) has shown that the parameters and quantile estimations vary randomly with the threshold value, and no single value is entirely adequate.…”
Section: Probability Distributions Used To Adjust Pdsmentioning
confidence: 99%
“…Various pds have been fitted to PS discharges including exponential (Cunnane 1973, Madsen et al 1997 and log Pearson 3 (Jayasuriya and Mein 1985). The generalized Pareto (GP) pd is a popular choice with its merits demonstrated in the late 1920s (Fisher andTippet 1928 cited in Ribatet et al 2007).…”
Section: Introductionmentioning
confidence: 99%